Surface topography and the impact on fatigue performance. (2nd March 2015) - Ardi, D T; Li, Y G; Chan, K H K; Blunt, L; Bache, M R
Abstract: Areal characterization was applied to plain fatigue specimens manufactured from a nickel-based superalloy, Alloy 720Li, to determine the impact of machined/finished surface topography on fatigue performance of this material. Samples were subjected to fatigue testing in the as-turned and shot peened conditions to study the interaction between residual stresses and topography in influencing the fatigue performance. The turning process was deliberately manipulated to produce three distinct finishes which were subsequently given an identical shot peening, resulting in six grades of surface topography. Surface topography was found to influence fatigue even in the presence of peened compressive residual stresses by promoting crack initiation at valley sites. Both the roughness amplitude and spatial characteristics of the surface were found to be important when correlating to fatigue performance.